Determinants of Pakistan’s Exports: An Econometric Analysis - Jadoon, Arshad Ullah; Guang, Yangda; Ahmad, Anwar; Ali, Sajad (Comparative Economic Research. Central and Eastern Europe, 2018)
The research investigated the determinants of Pakistan’s exports by using time series data from 1990–2016. Certain econometric tests were also applied to check cointegration among variables. A unit root test was used to check the stationarity of selected variables. After the stationarity of the data, a vector error correction model is used to estimate the effect of regressors, like foreign direct investment, gross domestic product, employment level, and consumption expenditures on a dependent variable, i.e. exports in the short run. The result shows the positive relationships that foreign direct investment, gross domestic product and employment level have on exports, and the adverse impact of consumption expenditures on the dependent variable. The study uses Johansen’s cointegration test for the long run. The results show that all the variables are co‑integrated in the long run. It is suggested that the government should encourage foreign direct investment and gross domestic product, which would help accelerate Pakistan’s exports. It is also suggested that whenever policymakers provide a trade policy, in particular, in relation to exports, then the adverse effect of exchange rate depreciation, external debt burdens, taxes, sanctions and protectionism should be quantified, and necessary measures be suggested so as to minimize any repercussions.